Prenatal Diagnosis of Glutaric Acidemia I Based on Amniotic Fluid Samples in 42 Families Using Genetic and Biochemical Approaches - Xiao, Bing; Qiu, Wenjuan; Ye, Jun; Zhang, Huiwen; Zhu, Hong; Wang, Lei; Liang, Lili; Xu, Feng; Chen, Ting; Xu, Yan; Yu, Yongguo; Gu, Xuefan; et al. (Frontiers in Genetics, 2020)
Direct mutation analysis is the major method for glutaric acidemia I (GA-I) prenatal diagnosis, while systemic application of a biochemical strategy is rare. We describe our experiences with metabolite measurement together with mutation analysis in GA-I prenatal diagnosis at a single center over 10 years.The data of genetic analysis and metabolite measurement using gas chromatography/mass spectrometry(GC/MS) and tandem mass spectrometry(MS/MS) in amniotic fluid samples of 44 fetuses from 42 GA-I families referred to our center from 2009 to 2019 were retrospectively analyzed.Among these 44 fetuses, genetic and biochemical results were both available in 39 fetuses. Of these, 6 fetuses were judged as affected and 33 fetuses as unaffected by mutation analysis. The levels of glutarylcarnitine (C5DC), C5DC/octanoylcarnitine (C8), and glutaric acid in the supernatant of amniotic fluid from affected fetuses were significantly higher than those in unaffected fetuses [1.73μmol/L (0.89–4.19) vs. 0.16μmol/L (0.06–0.37), 26.26 (12.4–55.55) vs. 2.23 (1.04–8.44), and 103.94 mmol/mol creatinine (30.37–148.31) vs. 1.01mmol/mol creatinine (0–9.81), respectively; all P<0.0001]. Among all families, two were found to have one causative mutation in the proband, in four pregnancies from these two families, three fetuses were judged as “unaffected” and one was judged as “affected” according to metabolites results. Postnatal follow-up showed a normal phenotype in all unaffected fetuses judged by mutation or metabolite analysis. C5DC, C5DC/C8, and glutaric acid levels in the supernatant of amniotic fluid showed significant differences and no overlap between the affected and unaffected fetuses. Biochemical strategy could be implemented as a quick and convenient method for the prenatal diagnosis of GA-I.